1989
DOI: 10.1093/jac/23.suppl_c.197
|View full text |Cite
|
Sign up to set email alerts
|

Urinary recovery and tolerability of FCE 22101 following single intravenous administration under restricted and high fluid intake

Abstract: The urinary recovery and tolerability of FCE 22101, a broad spectrum injectable penem, were investigated in a multicentre single-blind randomized crossover study of 60 healthy male volunteers. Single 1 g doses of FCE 22101 or placebo were given by intravenous bolus at weekly intervals. FCE 22101 was given either after intake of 750 ml water (treatment A) or after 8 h of water restriction (treatment B). Placebo was given under water restriction (treatment C). Urine samples obtained at timed intervals were assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is of interest to note that some subjects in study 1 who reported complaints of the urinary tract had lower urinary recoveries than the other subjects in the same group. A successive study was performed to examine if the frequency of these symptoms could be influenced by water intake or by the concentration of FCE 22101 metabolites in urine (19). The study showed that water intake could not completely prevent these symptoms but could decrease their incidence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest to note that some subjects in study 1 who reported complaints of the urinary tract had lower urinary recoveries than the other subjects in the same group. A successive study was performed to examine if the frequency of these symptoms could be influenced by water intake or by the concentration of FCE 22101 metabolites in urine (19). The study showed that water intake could not completely prevent these symptoms but could decrease their incidence.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, careful microscopic examinations of urinary sediments in the study subjects indicated no crystalline production. One result of the tolerance study (19) was that bladder symptoms were associated with low urinary recovery of FCE 22101 and its main metabolite, P1. Thus, it was hypothesized that symptoms are associated with high rates of drug metabolism in the kidney and that local irritation is probably caused either by a metabolite still to be detected or by degradation products of P1.…”
Section: Resultsmentioning
confidence: 99%